Student’s Learning Profile as a Tool of Personal Learning Logistics - M. E. Kushnir; P. D. Rabinovich; K. E. Zavedenskiy; I. S. Tsarkov (Высшее образование в России)
Increase of complexity and uncertainty as well as demand for personalization (including in education) urges universities to pay attention to educational subjectivity and its development; to transfer towards individual / collective-individual educational navigation and flexible systems of educational programs management (including formation of temporary learning groups, supply of required educational resources in due time, protocols of appraisal and mutual offset of educational results), what determines the relevance of the research. Usage of logistic approach enables to distinguish the pedagogical and management objectives of educational activity organization as well as to facilitate personalization of education. The article considers an educational profile as an instrument of personal educational logistics in digital educational environment, presents the preliminary terms “digital track”, “portfolio”, “profile”. The authors also dwell on the requirements to educational profiles development and scenarios of handling them in digital educational environment taking into account domestic and global experience of educational profiles’ implementation.